2019
DOI: 10.1111/mmi.14194
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of crust proteins to spore surface properties in Bacillus subtilis

Abstract: Summary Surface properties, such as adhesion and hydrophobicity, constrain dispersal of bacterial spores in the environment. In Bacillus subtilis, these properties are influenced by the outermost layer of the spore, the crust. Previous work has shown that two clusters, cotVWXYZ and cgeAB, encode the protein components of the crust. Here, we characterize the respective roles of these genes in surface properties using Bacterial Adherence to Hydrocarbons assays, negative staining of polysaccharides by India ink a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(87 citation statements)
references
References 58 publications
5
74
0
Order By: Relevance
“…The percentage of spores remaining in the aqueous layer is obtained by comparing the optical densities of the spore suspension before and after vortexing. All three methods were used recently to determine the roles played by crust structural proteins in these properties (22). Previous work has revealed that the last four genes in the spsA-L operon encode enzymes involved in rhamnose biosynthesis during the late stages of sporulation (8).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The percentage of spores remaining in the aqueous layer is obtained by comparing the optical densities of the spore suspension before and after vortexing. All three methods were used recently to determine the roles played by crust structural proteins in these properties (22). Previous work has revealed that the last four genes in the spsA-L operon encode enzymes involved in rhamnose biosynthesis during the late stages of sporulation (8).…”
Section: Resultsmentioning
confidence: 99%
“…In this article, we continue a line of research initiated when we investigated how spore surface properties were influenced by the structural proteins responsible for proper crust assembly, focusing on cotO and cotVWXYZ (22). The deletion of these genes greatly disrupted the crust structure, resulted in perturbations of the PS distribution around the spore, and caused modifications in the hydrophobicity of the spore surface.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the outermost B. subtilis spore layer, termed the crust, contains both proteins and carbohydrate, giving a matrix outside the coat protein layer (27). However, the precise structure and composition of the crust layer are not known, and the spore crust would be expected to be greatly reduced in severely coat-defective spores such as PS4150, which lacks the coat morphogenic protein CotE, as well as the GerE transcription factor for many coat protein genes (19,27). In principle, Tb 3ϩ /Dy 3ϩ could bind to either carboxylate groups or phosphate groups on either a sugar or a protein backbone.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, four isogenic B. subtilis strains were used with the PY79 genetic background, including PS3483 (the wild-type strain), PE620 lacking the cotXYZ operon, PE2763 lacking spsI, and PE2916 lacking cgeB. The latter three strains were obtained from Patrick Eichenberger, and each lacks various components of the spores' outermost crust layer (27). The B. cereus strain T was originally obtained from H. O. Halvorson.…”
Section: Methodsmentioning
confidence: 99%